EUGENICS: SCIENCIE AND RELIGION. AN APPROACH TO THE CHILEAN CASE - Sánchez Delgado, Marcelo (Revista de Historia Social y de las Mentalidades, 2015)
The work aims to investigate the relationships of continuity and tension between the modern project, religious thought and the eugenic thinking in the Chilean context. The work begins with a general reflection on the relationship between eugenics and religion in the modern context, and then engages with primary sources that includes works by lawyers and physicians of the first half of the chilean twentieth century. The main result of the study shows that the discussion of eugenic thought in the national context was no stranger to religious, utopian and mystifying forces, which tends to see eugenics as the religion of the future and as a thinking alternative and critical of Christianity. Moreover, also stands out as a result of this work, a new appreciation of the relationships between Catholicism and eugenics in the Chilean context.